2018
DOI: 10.31616/asj.2018.12.4.720
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Peripheral Nerve Disease in Patients with Failed Lumbar Disc Surgery

Abstract: Study DesignRetrospective study (level of evidence=3).PurposeWe examine the relationship between residual symptoms after discectomy for lumbar disc herniation and peripheral nerve (PN) neuropathy.Overview of LiteraturePatients may report persistent or recurrent symptoms after lumbar disc herniation surgery; others fail to respond to a variety of treatments. Some PN neuropathies elicit symptoms similar to those of lumbar spine disease.MethodsWe retrospectively analyzed data for 13 patients treated for persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Elsewhere, 8) we reported that LDH patients with FBSS benefited from treatment of their peripheral nerve disease; their persistent or recurrent LBP and leg pain improved. These findings suggest that block treatment for coexisting PLSD may be effective in patients with LDH.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Elsewhere, 8) we reported that LDH patients with FBSS benefited from treatment of their peripheral nerve disease; their persistent or recurrent LBP and leg pain improved. These findings suggest that block treatment for coexisting PLSD may be effective in patients with LDH.…”
Section: Discussionmentioning
confidence: 84%
“…LDH patients with cauda equina syndrome and severe or progressive neurological symptoms are also surgical candidates. 8) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, bleeding control is one of the factors affecting successful clinical outcomes after spine surgery. Owing to recent developments in the techniques of minimally invasive spine surgery and advancements in endoscope-related optical technology, BESS was introduced, and numerous results have been reported [8][9][10][11][12][13]. Because it has surgical indications similar to those in conventional open surgery, BESS is gaining interest recently as a minimally invasive spine surgery technique with favorable outcomes similar to those of microscopic decompression in spinal stenosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of an endoscope has gained interest in the field of minimally invasive surgery. For the treatment of spinal stenosis, biportal endoscopic spine surgery (BESS) was introduced as an alternative method for microscopic unilateral laminotomy for bilateral decompression (ULBD) [8][9][10][11][12][13]. The basic concept of the BESS is similar to those of arthroscopic and laparoscopic surgeries, in which an endoscope is inserted through a viewing portal, and surgical instruments are inserted into a separate working portal.…”
Section: Introductionmentioning
confidence: 99%